Преступления против личности: лекции / Е. В. Благов - Благов Евгений Владимирович (Юрлитинформ, 2010)
Экземпляры: КХ (20101006) / Инвентарный номер: 1080862 / Цена: / Сис.шифр: 67.408 / Авт.знак: Б 68 / ГРНТИ: 10 / ББК: 67.408.11